Rapid ice margin fluctuations during the Younger Dryas in the tropical Andes - Rodbell, D. T.; Seltzer, G. O. (Quaternary Research, 2000)
Radiocarbon dated lacustrine sequences in Peru show that the chronology of glaciation during the late glacial in the tropical Andes was significantly out-of-phase with the record of climate change in the North Atlantic region. Fluvial incision of glacial-lake deposits in the Cordillera Blanca, central Peru, has exposed a glacial outwash gravel; radiocarbon dates from peat stratigraphically bounding the gravel imply that a glacier advance culminated between similar to 11,280 and 10,990 C-14 yr B.P.; rapid ice recession followed. Similarly, in southern Peru, ice readvanced between similar to 11,500 and 10,900 C-14 yr B.P. as shown by a basal radiocarbon date of similar to 10,870 C-14 yr B.P. from a lake within 1 ion of the Quelccaya Ice Cap. By 10,900 C-14 yr B.P, the ice front had retreated to nearly within its modern limits. Thus, glaciers in central and southern Peru advanced and retreated in near lockstep with one another. The Younger Dryas in the Peruvian Andes was apparently marked by retreating ice fronts in spite of the cool conditions that are inferred from the partial derivative O-18 record of Sajama ice. This retreat was apparently driven by reduced precipitation, which is consistent with interpretations of other paleoclimatic indicators from the region and which may have been a nonlinear response to steadily decreasing summer insolation. (C) 2000 University of Washington.
388erTimes Cited:61Cited References Count:66